THE USE OF GAME TECHNOLOGIES IN RUSSIAN LANGUAGE LESSONS - Джумаева Светлана Хайдаровна (Bright Mind Publishing, 2025)
The article discusses modern game technologies used in Russian language lessons. Their pedagogical capabilities for increasing students' motivation, developing communication skills, creative thinking and active participation in the educational process are analyzed. It is noted that the use of game elements, such as work in pairs and groups, role-playing games, competitions and interactive exercises, contributes to more effective assimilation of educational material, supports positive emotional mood and forms a stable interest in studying the Russian language in students. Practical recommendations for the introduction of game methods in the educational process are given.
Keywords: Game technologies, Russian language lesson, pedagogical methods, student motivation, communication skills, interactive learning.